CORNERSTONE’s Silicon Photonics Rapid Prototyping Platforms: Current Status and Future Outlook - Callum G. Littlejohns; David J. Rowe; Han Du; Ke Li; Weiwei Zhang; Wei Cao; Thalia Dominguez Bucio; Xingzhao Yan; Mehdi Banakar; Dehn Tran; Shenghao Liu; Fanfan Meng; et al. (Applied Sciences, 2020)
The field of silicon photonics has experienced widespread adoption in the datacoms industry over the past decade, with a plethora of other applications emerging more recently such as light detection and ranging (LIDAR), sensing, quantum photonics, programmable photonics and artificial intelligence. As a result of this, many commercial complementary metal oxide semiconductor (CMOS) foundries have developed open access silicon photonics process lines, enabling the mass production of silicon photonics systems. On the other side of the spectrum, several research labs, typically within universities, have opened up their facilities for small scale prototyping, commonly exploiting e-beam lithography for wafer patterning. Within this ecosystem, there remains a challenge for early stage researchers to progress their novel and innovate designs from the research lab to the commercial foundries because of the lack of compatibility of the processing technologies (e-beam lithography is not an industry tool). The CORNERSTONE rapid-prototyping capability bridges this gap between research and industry by providing a rapid prototyping fabrication line based on deep-UV lithography to enable seamless scaling up of production volumes, whilst also retaining the ability for device level innovation, crucial for researchers, by offering flexibility in its process flows. This review article presents a summary of the current CORNERSTONE capabilities and an outlook for the future.